Sequencing for novel mutation screening in juvenile polyposis syndrome - Nattapon Khongcharoen; Wison Laochareonsuk; Pongsakorn Choochuen; Wanwisa Maneechay; Surasak Sangkhathat (Elsevier, 2022)
Introduction: Juvenile polyposis syndrome (JPS), a rare polyposis syndrome in childhood, is characterized by multiple diffuse hamartomatous polyps in the gastrointestinal tract (GI) with an estimated incidence of one in 50,000 to 100,000 live births. Although a juvenile polyp is a non-cancerous lesion, affected individuals have an increased risk of GI malignancy. JPS is a disease related to loss-of-function mutations in BMPR1A and SMAD4 involved in the biological maintenance of cellular growth. Pathogenic mutations in those genes have been identified in approximately 50-60% of JPS cases. Presentation: Our report describes two JPS cases with loss-of-function mutations of BMPR1A identified by a high-throughput nucleotide sequencing. Both cases had a similar clinical manifestation, symptomatic lower GI bleeding. Both patients underwent a total colectomy after histological confirmation. Consequently, Family members who had had genetic confirmation of these mutations were invited to be screened by enteroscopy. Conclusion: JPS is a hereditary disease caused by dominantly inherited loss-of-function of the BMPR1A and SMAD4 genes. Identifying loss-of-function mutations in particular genes allows early screening, diagnosis, and prevention of malignancy among the index cases and their families. High-throughput genome sequencing is a current molecular approach for improving the precision of mutation detection and minimizing time to diagnosis.